?omparative Analysis of Human Kidney Venous Vessels at Various Method of Radiation Research - Abuselim Vezirkhanov1, Edgar Kafarov1, Oleg Zenin1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the study was to conduct a comparative assessment of the spatial characteristics of the kidneyveins in a planar projection, in stereo projection, and according to the results of computed tomography after3D modeling. To compare and identify the truth of the morphometric parameters of the renal veins, as wellas the options for their formation during x-ray and computed tomography, 136 corrosive preparations of thekidney veins were made, which were taken as a control group. To identify the degree of similarity of the renalveins parameters on corrosion preparations, X-ray diffraction patterns (2D) and on computed tomograms(CT) with a helix pitch of 1.0 and 2.5 mm after 3D modeling, a comparative assessment of the obtainedparameters was performed (degree of the angle similarity - simPhi; the degree of length similarity is simLen;and the general degree of similarity is sim). It was revealed that the greatest degree of parameters similaritywas found between corrosive preparations and computed tomograms of kidney veins with a spiral pitch of1.0 mm, which was 98.0%. Studies have shown that the informational content of x-ray examination of thekidneys’ veins depends on the options for the formation and location of blood vessels in the gates of thekidney relative to the frontal, horizontal and sagittal planes. The informativeness of computed tomographystudies does not depend on the options for the formation of renal veins, it determines the step of the spiral